Macroeconomic convergence of EU member states - Khokhrunov, Daniil; Formánek, Tomáš; Sokol, Ondřej; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This work is dedicated to macroeconomic convergence in EU member states. Processes of both β- and σ convergence are studied on country-level using combination of clustering and LME methods. Results are in favour of β-convergence. However there was no strong evidence of consistent σ-convergence found. Robustness of results was tested against different cluster-structures, length of time periods and first chosen year of data for the analysis. Also an alternative augmented model with additional variables was proposed. However, in such augmented model not much of additional explanatory power added by additional variables was found, hence a Theoretically derived LME model was preffered. Except for basic convergence, methodology was used to study effects that Global Financial Crisis (2008) had on convergence processes. It was found, that in post-crisis period the speed of β-convergence became faster, which was likely caused by common anti-crisis policies. Lastly, real-world alliances were analyzed, sinse those could be considered to be naturally formed clusters. It was found, that generally, the speed of β-convergence in such natural clusters is faster than in artificially composed clusters. Generally, there was found an evidence of strong β-convergence in EU member states, however there was no evidence of consistent σ-convergence found
Vedoucí práce: Tomáš Formánek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: ekonometrie a operační výzkum [obor dipl. práce]; diplomové práce; master's theses